2018
DOI: 10.1111/anae.14320
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis and trial sequential analysis of local vs. general anaesthesia for carotid endarterectomy

Abstract: Controversy exists regarding the best choice of anaesthesia for carotid endarterectomy. We aimed to evaluate the peri-operative outcomes of local vs. general anaesthesia for carotid endarterectomy. We conducted a systematic search of electronic information sources and applied a combination of free text and controlled vocabulary searches adapted to thesaurus headings, search operators and limits in each of the electronic databases. We defined peri-operative stroke, transient ischaemic attack, mortality and myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Three major meta-analyses have been performed in an effort to resolve this issue. [43][44][45] Two of these studies 43,45 concluded that LA was associated with significantly lower stroke and mortality rates, but the remaining study by Vaniyapong et al, 44 which included only RCTs, found no significant difference in outcomes between LA and GA. This current study, with a total sample size of 152,376, represented a much bigger population than any of the previous meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three major meta-analyses have been performed in an effort to resolve this issue. [43][44][45] Two of these studies 43,45 concluded that LA was associated with significantly lower stroke and mortality rates, but the remaining study by Vaniyapong et al, 44 which included only RCTs, found no significant difference in outcomes between LA and GA. This current study, with a total sample size of 152,376, represented a much bigger population than any of the previous meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…This goes along with findings from previous meta-analyses that included nonrandomized studies. 43,45 However, the nonsignificant difference in the RCT subgroup analysis suggested possible bias in nonrandomized studies that were eliminated in the RCTs. Although DM and hypertension were well-established cardiovascular risk factors in general a prospective cohort study has failed to demonstrate any statistically significant differences between the morbidities in patients with or without these risk factors, 46 implying that this is less likely to be a confounder in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Der Vergleich von Lokal-und Allgemeinanästhesie während offener Karotischirurgie ergab keinen eindeutigen Vorteil vonLokalanästhesie hinsichtlichdes Auftretens postoperativer zerebrovaskulärer Ereignisse [55][56][57]. Unterschiedliche Anästhesieverfahren, u. a. Analgosedierung, Spinal-und Epiduralanästhesie, wurden mit einer Allgemeinanästhesie während der endovaskulären Versorgung von abdominalen Aortenaneurysmen in prospektiven Beobachtungsstudien verglichen.…”
Section: Wahl Des Anästhesieverfahrensunclassified
“…[4] Although not yet proven in randomized clinical trials, CEA under local anesthesia has been suggested to reduce perioperative morbidity and mortality in the latest reports. [5] In this study, we present our personal singlesurgeon experiences regarding CEA procedures performed under local anesthesia.…”
mentioning
confidence: 99%